2004
DOI: 10.1590/s1415-47572004000200015
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and morphological studies of diploid and polyploid cytotypes of Stevia rebaudiana (Bertoni) Bertoni (Eupatorieae, Asteraceae)

Abstract: In this study, we examined the chromosome number and some morphological features of strains of Stevia rebaudiana. The chromosomes were analyzed during mitosis and diakinesis, and the tetrad normality and pollen viability were also assessed. In addition, stomata and pollen were measured and some plant features were studied morphometrically. All of the strains had 2n = 22, except for two, which had 2n = 33 and 2n = 44. Pairing at diakinesis was n = 11 II for all of the diploid strains, whereas the triploid and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
1
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 15 publications
2
34
1
10
Order By: Relevance
“…The result of the analysis for character correlation was shown that some characters, closely related to yield, first of all were dry leaf weight, fresh leaf weight, fresh culm weight, dry culm weight per plant, then, culm width, number of branch, and the third, plant height, number of nod, paired leaf number before transplanting. The results agree with Oliveira et al (2004) who examined some morphological features of strains of Stevia rebaudiana. Amino acid composition of Stevia rebaudiana (g 100 -1 dry matter) Data in Table 3 for essential and non essential amino acid composition in Stevia rebaudiana under different salt concentrations 1.58, 2.58, 5.2, 6.60, 10.17 and 13.7 EC indicated that with the increase in salt levels the value of both Valine and Proline were increased from 0.71 and 0.020 to 1.70 and 1.78 g 100 -1 dry matter, in respect with range 0.99 and 1.61 g 100 -1 dry matter, respectively.…”
Section: Results and Discussion Morphological Studies Of Stevia Rebasupporting
confidence: 90%
“…The result of the analysis for character correlation was shown that some characters, closely related to yield, first of all were dry leaf weight, fresh leaf weight, fresh culm weight, dry culm weight per plant, then, culm width, number of branch, and the third, plant height, number of nod, paired leaf number before transplanting. The results agree with Oliveira et al (2004) who examined some morphological features of strains of Stevia rebaudiana. Amino acid composition of Stevia rebaudiana (g 100 -1 dry matter) Data in Table 3 for essential and non essential amino acid composition in Stevia rebaudiana under different salt concentrations 1.58, 2.58, 5.2, 6.60, 10.17 and 13.7 EC indicated that with the increase in salt levels the value of both Valine and Proline were increased from 0.71 and 0.020 to 1.70 and 1.78 g 100 -1 dry matter, in respect with range 0.99 and 1.61 g 100 -1 dry matter, respectively.…”
Section: Results and Discussion Morphological Studies Of Stevia Rebasupporting
confidence: 90%
“…TTC is accepted by the International Rules for Seed Testing (ISTA) as a chemical for testing seed viability (1999). This method has been effectively utilized across a wide range of plant species to predict germination and growth of seedling (Oliveira, Forni-Martins, Magalhães, & Alves, 2004). …”
Section: Seed Viabilitymentioning
confidence: 99%
“…for Iris fulva in flower traits (Inoue et al 2006), for Allium scorodoprasum in number of flowers and size of stomata (Murin & Ferakova 1988), for Fagopyrum tataricum in grain size (Oba et al 2004), and for Stevia rebaudiana in pollen and stomata size (Oliveira et al 2004). Phenotypic difference of Allium oleraceum cytotypes is stated only in plant size in mixed populations (Åström & Haeggström 2003).…”
Section: Introductionmentioning
confidence: 99%